Inégalités écologiques et comportement électoral : le cas des élections municipales françaises de 2001 - Etienne Farvaque; Nicolas Jean; Bertrand Zuindeau (Développement Durable et Territoires)
This paper studies the impact of environmental conditions on the result of incumbent parties' candidates in the 2001 local election in France. Our sample covers 560 towns. Starting from an econometric model of vote adapted for French specificities, we first confirm the presence of an partisan incumbency premium. We also find that the electorate penalizes the incumbent party for ozone and ground pollution. More paradoxically, the presence of underground or tramway lines appears more as an indicator of congestion than of a better quality of life, and is thus electorally costly.